Pseudoaneurisma gigante de artéria esplênica - Torres,Orlando Jorge Martins (2004)
Splenic artery pseudoaneurysm larger than 10 cm is a rare condition. The risk of rupture is probably high and surgical treatment is necessary. The objective of this article is to report a case of a patient with giant pseudoaneurysm of the splenic artery submitted to surgical resection. A 26-year-old man complaining of gastrointestinal hemorrhage and abdominal pain The patient’s medical history revealed that one year before he had an abdominal blunt trauma. The angiography showed a giant pseudoaneurysm of the splenic artery with compression of the stomach. The patient was operated on by abdominal access and the spleen and pseudoaneurysm were resected. The postoperative course was uneventful and the patient was discharged 13 days after surgery without problems.